STRATEGI PEMBERDAYAAN EKONOMI MASYARAKAT BERBASIS INOVASI OLAHAN REBUNG DI DESA LOYOK - Hendry Tira; Putri Nurul Hikmah; Anisa Lailatun Najwa; Fia Afriani; Mulawarman; Prautama Yuda; Aisa Aulia Kartini; Sari Maulidiana; Detha Wahyu Aglia Musta; Fathurrahman; Syi’ra Banu Ramadhani (Jurusan Teknik Elektro Universitas Mataram, 2026)
The University of Mataram Community Service Program (KKN) in Loyok Village, East Lombok Regency, aims to empower the community through the optimal and sustainable utilization of local bamboo potential. Previously, bamboo in the village had been utilized primarily for woven crafts, while the food potential of bamboo shoots had not been fully developed. Through a participatory approach, this program focused on product diversification by processing bamboo shoots into chips. Activities were carried out through training in processing, packaging, and business mentoring, as well as the introduction of digital technology for marketing and transactions. As a result, the Loyok Village community succeeded in producing new processed products with higher economic value, improving skills, and adopting the principles of a circular economy and zero waste. This program not only increased community income but also strengthened the village's economic independence based on local wisdom. It was concluded that the innovation of processing bamboo shoot chips has the potential to become a sustainable flagship product of Loyok Village with the support of consistent and integrated management.